Substantiation of the teaching of medical ethics and bioethics clinic - Mendoza Fernández, Alfonso (2009)
In this paper we try to substantiate the need for including medical ethics and clinical bioethics in the studying plan for medical schools. This need arises because of the brand new situations generated by the current medical technology developments, which oblige us to be particularly respectful in dealing with bioethical principles and with the rights of human beings in order to have the most adequate framework for decision making with respect to medical procedures or interventions. We also discuss the teaching-learning processes, the adequate timing for teaching medical ethics, and the role of medical school teachers for achieving their educational and research objectives.